(untitled) (Jurnal Teknologi Industri Pertanian, 2026)
This study explores how digital technology enhances innovation performance through open innovation (OI) among agro-SMEs in Depok, Indonesia. Using a qualitative approach, data were collected through semi-structured interviews, field observations, and documentation from an AI-focused digital training program. Thematic analysis using NVivo revealed five main themes: digital collaboration, peer learning, knowledge sharing, innovation drivers, and competitiveness. Findings indicate that digital tools, such as social media, e-commerce platforms, and simple AI applications, facilitate knowledge exchange and co-creation with customers, suppliers, and peer SMEs. Peer-based learning and informal collaboration during community events and training significantly enhanced product improvements and branding innovations. However, barriers are still existing, such as limited digital skills, low confidence, and a lack of structured support, hinder the full adoption of digital OI practices. This study underscores the importance of localized innovation ecosystems and practical support mechanisms in enabling SMEs to engage in open innovation. A strategic framework linking digital knowledge flows and collaborative capabilities to innovation performance is proposed. The results offer practical guidance for institutions and policymakers seeking to strengthen SME competitiveness in the agricultural sector. Keywords: agro-SMEs, collaboration, open innovation, digital technology, innovation performance, knowledge exchange